Publishing Strategies of Translated Children’s Literature in Argentina: A Combined Approach - Alvstad, Cecilia (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2003)
AbstractThis article is a presentation of the general framework of a research project in which 56 translated and 94 non-translated books published for children in Argentina during 1997 are analyzed. In the project, the translated books are compared with the non-translated ones from paratextual, literary and linguistic viewpoints. Translation is considered to be a decision-making process and the broad approach proposed here makes possible a comparison of the decisions taken by publishers and translators in different areas and, most importantly, to the interrelations of these decisions. The results will increase the general knowledge of translation for children and of literature published for children in an Argentinean context. Moreover, they will be of importance for methodological issues such as the selection of corpora.